Implikasi Signalling Theory atas Pengumuman Pembagian Dividend Cuts terhadap Reaksi Pasar - Dian Indri Purnamasari (Jurnal Akuntansi dan Bisnis, 2006)
There were so many dicussions about how divident can influence value of a firm that have to be considered. Many studies approved that divident announcement can cause security buying rise fastly, but there is reducing in security selling. The amount of divident sometimes apreciated by investor as a signal. The problem is: Is the divident-cuts announcement always apreciated by investors as a bad news, so their reaction is bad? Actually, market (investors) didn’t always react negatively agains divident-cuts announcement, and didn’t always apreciate it as a bad-signal. Market could see another information content behind the bottom line of divident-cuts announcement. Market did’t see information content from bottom line information only, but also from another information content that cause firm made a divident-cut policy.